2017
DOI: 10.1111/jeb.13213
|View full text |Cite
|
Sign up to set email alerts
|

Stronger selective constraint on downstream genes in the oxidative phosphorylation pathway of cetaceans

Abstract: The oxidative phosphorylation (OXPHOS) pathway is an efficient way to produce energy via adenosine triphosphate (ATP), which is critical for sustaining an energy supply for cetaceans in a hypoxic environment. Several studies have shown that natural selection may shape the evolution of the genes involved in OXPHOS. However, how network architecture drives OXPHOS protein sequence evolution remains poorly explored. Here, we investigated the evolutionary patterns of genes in the OXPHOS pathway across six cetacean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…UQCRQ is identified as a small core-associated protein and a subunit of ubiquinol-cytochrome c reductase complex III [ 37 ]. Although no report showed that UQCRQ is directly related to NAFLD, UQCRQ is associated with oxidative phosphorylation pathway [ 38 ]. Based on the relationship between oxidative phosphorylation and NAFLD, we speculate that UQCRQ is linked to NAFLD and may be a key gene in the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…UQCRQ is identified as a small core-associated protein and a subunit of ubiquinol-cytochrome c reductase complex III [ 37 ]. Although no report showed that UQCRQ is directly related to NAFLD, UQCRQ is associated with oxidative phosphorylation pathway [ 38 ]. Based on the relationship between oxidative phosphorylation and NAFLD, we speculate that UQCRQ is linked to NAFLD and may be a key gene in the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria function to supply cellular energy and produce heat and are therefore extremely sensitive to heat and energy-related selective pressure [ 1 , 19 22 ]. The role of selection in the evolution of mitochondrial DNA (mtDNA) attracted little attention until recently [ 3 , 9 , 23 , 24 ]. Mitochondrial OXPHOS genes have been shown to display evidence of adaptive evolution in, for example, dogs, bats, birds and fishes [ 21 , 22 , 25 , 26 ], and numerous studies have detected signals of positive selection in mitochondrial genes [ 21 23 , 27 ], suggesting positive selection plays a strong potential role in adaptation [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…QCR8 (encoded by Uqcrq) is a small core-associated protein and a subunit of ubiquinol-cytochrome c reductase complex III associated with the oxidative phosphorylation pathway. Intriguingly, Zeng et al [76] found a potential relationship with the pathogenesis of non-alcoholic steatohepatitis, although the mechanistic process remains obscure. Tian et al [77] nevertheless revealed this protein is strongly associated with hypoxia stress resistance, a point of great interest in the context of the liver metabolic changes associated with metastatic liver colonization.…”
Section: Heme Biosynthesis and Electron Transport Chainmentioning
confidence: 99%